Lasting effects of adaptive visual reweighting on postural control in young adults - Genoves, Giovanna Gracioli [UNESP]; Barela, Ana Maria Forti; Aguiar, Stefane Aline; Barela, José Angelo [UNESP] (American Psychological Association (APA), 2017)
Postural control involves the use of sensory cues that must be properly integrated to provide specific information to accommodate continuous changes in the environment. Studies have shown several features of adaptive sensorimotor behavior, but many of the mechanisms are still unknown, such as perdurable effects. The purpose of the present study was to examine the lasting effects of visual reweighting adaptation on postural control in young adults. Seventeen young adults were exposed to a moving room situation in 3 experimental sessions that occurred on different occasions. In the first occasion, participants were exposed to seven 60-s trials, in which the room oscillated sinusoidally (0.2 Hz). The first 3 trials and last 3 trials had an amplitude of 0.6 cm and velocity of 0.6 cm/s (peak-to-peak). The fourth trial had an amplitude of 3.5 cm and velocity of 3.5 cm/s (change trial). In the second and third occasions, 1 and 7 days after the first occasion, respectively, the participants performed 3 trials with the room moving with the same parameters as the first trial in the first occasion. The results indicated that the abrupt increases in amplitude and velocity led to a less coherent and smaller magnitude of postural response to the moving room. The reduction of the induced postural response that was caused by visual manipulation lasted at least 1 week. These results suggest that adaptive changes that are caused by environmental changes are maintained for a relatively long period of time in young adults.
Keywords: Moving room; Posture; Reweighting; Sensorimotor adaptation; Visual manipulation